Dampak Program Bantuan Produktif Usaha Mikro Terhadap Pendapatan Pelaku Usaha Mikro - Nurrahma, Fahrisa; Khotimah, Khusnul; Islamay, Sifa Veronica (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The Covid-19 pandemic has had a major effect on the economic sector, especially in MSMEs. As a result, many MSMEs have been affected by the Covid-19 pandemic, one of which is business actors in Wahas Village. As a result, the government carried out national economic recovery, one of which was by providing Micro Business Productive Assistance (BPUM). This assistance is given to business actors to be able to re-support their business capital. The formulation of the problem in this paper is how the benefits and procedures for distributing the BPUM program reach the community. then also reviewed how the impact of this program on people's income after getting BPUM. The purpose of this paper is to find out how the impact of government assistance programs on the income of business actors in Wahas Village. The method used is a type of qualitative descriptive research method. The data sources used are primary and secondary data sources. Data was collected using observation, interviews and documentation.The result of this research is the BPUM procedure starting from the proposal, data cleaning, searching and monitoring, while the effect is that the provision of business capital through the BPUM program does not affect the income of BPUM recipients.